Changing epidemiology of shigellosis in Taiwan, 2010-2019: an emerging threat to HIV-infected patients and men who have sex with men. Issue 1 (31st December 2022) - Tsai, Chin-Shiang; Lin, Kuan-Yin; Liou, Bo-Huang; Chiou, Chien-Shun; Lin, Yi-Chun; Lee, Yuan-Ti; Yang, Chia-Jui; Tang, Hung-Jen; Liao, Ying-Shu; Liu, Chun-Eng; Lee, Chen-Hsiang; Lu, Po-Liang; et al.
ABSTRACT: Shigellosis appears to increase in certain at-risk populations in developed countries. Based on the nationwide surveillance, the annual incidence of shigellosis in Taiwan (1999-2019) was 0.38-5.77 cases per 100, 000 people. Indigenous shigellosis has mostly affected men who have sex with men (MSM) and people living with HIV (PLWH) since 2015. In this retrospective study, compared with those diagnosed before 2015, indigenous cases diagnosed during 2015–2019 mostly occurred in male adults (96.0% vs 47.1%, P  < 0.001), with a longer hospital stay (median 5.0 vs 3.5 days, P  = 0.029) and different coinfections. The predominant strains in 2015 and 2016 were ciprofloxacin-resistant Shigella sonnei and azithromycin non-susceptible Shigella flexneri ( S. flexneri ) 3a, which had been replaced by ciprofloxacin-resistant S. flexneri 2a since 2018. Notably, six indigenous cases were caused by cefotaxime-resistant S. flexneri . Inappropriate use of empiric antibiotic treatment was common. In conclusion, there is an ongoing spread of ciprofloxacin-resistant shigellosis among PLWH and MSM and cefotaxime-resistant S. flexneri is an emerging threat in Taiwan.